2022
DOI: 10.3389/fonc.2022.817635
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Alterations in Ocular Adnexal Mucosa-Associated Lymphoid Tissue Lymphoma With Whole-Exome Sequencing

Abstract: Next-generation sequencing studies on ocular adnexal marginal zone lymphoma of mucosa-associated lymphoid tissue (OAML) have to date revealed several targets of genetic aberrations. However, most of our current understanding of the pathogenesis and prognosis of OAML is primarily based on studies conducted in populations from Europe and the US. Furthermore, the majority were based on formalin-fixed paraffin-embedded (FFPE) tissue, which generally has poor integrity and creates many sequencing artifacts. To bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…IGLL5, encoding one of the immunoglobulin lambda-like polypeptides, frequently occurs in the mutation in cancer, including lymphoma, multiple myeloma, and chronic lymphoblastic leukemia. [20][21][22] Although the mutation rate of IGLL5 did not change with age, [23] Yao et al have shown that the low expression level of IGLL5 is a good diagnostic in elderly patients with late-onset major depressive disorder which increases the risk of suicide and disability in olds. [24] Therefore, we speculated that IGLL5 has a vital role in staying healthy for elders.…”
Section: Discussionmentioning
confidence: 99%
“…IGLL5, encoding one of the immunoglobulin lambda-like polypeptides, frequently occurs in the mutation in cancer, including lymphoma, multiple myeloma, and chronic lymphoblastic leukemia. [20][21][22] Although the mutation rate of IGLL5 did not change with age, [23] Yao et al have shown that the low expression level of IGLL5 is a good diagnostic in elderly patients with late-onset major depressive disorder which increases the risk of suicide and disability in olds. [24] Therefore, we speculated that IGLL5 has a vital role in staying healthy for elders.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway being one of the prominent activated pathways in the IgG4-ROD group supports the hypothesis of microorganisms being a conductor in the activation of inflammation leading to a chronic disease that exacerbates in IgG4-immunopositive plasma cell infiltration [ 50 ]. Furthermore, a recent next-generation sequencing study of orbital MALT lymphoma in an Asian population revealed a higher occurrence of somatic mutations in the NOD-like receptor signaling pathway, suggesting its importance in the oncogenesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%